Insecticidal activities of natural volatile compounds against pulse beetle, Callosobruchus chinensis (Bruchidae) - Chaubey, Mukesh Kumar (Acta Scientiarum. Biological Sciences, 2024)
Two pure natural volatile compounds, carvacrol and menthone were investigated for repellent, insecticidal, ovipositional and egg hatching inhibition activities against pulse beetle, Callosobruchus chinensis (Coleoptera: Bruchidae). Carvacrol and menthone repelled bruchid adults in choice oviposition assay. Both compounds caused toxicity, reduced oviposition potential and viability of eggs significantly when fumigated. In chronic toxicity assay, both carvacrol and menthone reduced F1 progeny production and weight loss in cowpea seeds. Reduced in grain damage was probably occurred due to inhibition of oviposition and egg hatching. Acetylcholine esterase enzyme activity was inhibited in adults when fumigated with carvacrol and menthone showing neurotic mode of action. Findings of the present study suggest that application of carvacrol and menthone can be effective in the management of C. chinensis.